Phenomics Research on Coronary Heart Disease Based on Human Phenotype Ontology. (14th December 2014) - Shi, Qi; Gao, Kuo; Zhao, Huihui; Wang, Juan; Zhai, Xing; Lu, Peng; Chen, Jianxin; Wang, Wei
Abstract : The characteristics of holistic, dynamics, complexity, and spatial and temporal features enable "Omics" and theories of TCM to interlink with each other. HPO, namely, "characterization, " can be understood as a sorting and generalization of the manifestations shown by people with diseases on the basis of the phenomics. Syndrome is the overall "manifestation" of human body pathological and physiological changes expressed by four diagnostic methods' information. The four diagnostic methods' data could be the most objective and direct manifestations of human body under morbid conditions. In this aspect, it is consistent with the connation of "characterization." Meanwhile, the four diagnostic methods' data also equip us with features of characterization in HPO. In our study, we compared 107 pieces of four diagnostic methods' information with the "characterization database" to further analyze data of four diagnostic methods' characterization in accordance with the common characteristics of four diagnostic methods' information and characterization and integrated 107 pieces of four diagnostic methods' data to relevant items in HPO and finished the expansion of characterization information in HPO.